2017
DOI: 10.1097/md.0000000000006577
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the chronic disease management program for appropriateness of medication adherence and persistence in hypertension and type-2 diabetes patients in Korea

Abstract: The chronic disease management program (CDMP), a multilevel intervention including copayment reduction and physician incentives, was introduced in 2012 in Korea to improve blood pressure and glycemic control by strengthening the function of clinic as primary care institutions in managing hypertension and diabetes. This study, therefore, aimed to evaluate the effect of CDMP on the appropriateness of medication adherence and persistence in hypertension or type-2 diabetes patients.A pre-post retrospective study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…In Koreans, chronic disease management programs (DM and HTN) improved both the adherence and persistence of treatment. 31 In addition, Putnam et al, 32 in a practice-based survey on hypertensive patients with type 2 diabetes achieved the target BP in 54% of the cases, whereas patients with low adherence to therapy were less likely to achieve target BP levels.…”
Section: Discussionmentioning
confidence: 99%
“…In Koreans, chronic disease management programs (DM and HTN) improved both the adherence and persistence of treatment. 31 In addition, Putnam et al, 32 in a practice-based survey on hypertensive patients with type 2 diabetes achieved the target BP in 54% of the cases, whereas patients with low adherence to therapy were less likely to achieve target BP levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research reported that mental health conditions (ie, depression, anxiety, and dementia) were important factors when analyzing treatment adherence and CVD events but lacked the ability to identify such mental conditions [73,74]. Many studies have used the Charlson Comorbidity Index [27-29] to explore the combined effects of comorbidities (ie, chronic obstructive pulmonary disease, depression, chronic kidney disease, and dementia), but this approach does not reflect the role of individual comorbidities. Furthermore, these studies did not control for duration of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, chronic illnesses such as type 2 diabetes, hypertension and cardiovascular disease have led to increasing healthcare costs, especially because chronic illnesses are frequently comorbid diseases (Kim et al. , ; Shin et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…In Korea, chronic illnesses such as type 2 diabetes, hypertension and cardiovascular disease have led to increasing healthcare costs, especially because chronic illnesses are frequently comorbid diseases (Kim et al 2014(Kim et al , 2017Shin et al 2015). Effective control and management of chronic illnesses require continuous, patient-centred and long-term care (Joo 2014).…”
Section: Introductionmentioning
confidence: 99%